2021
DOI: 10.3311/ppci.17672
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of the Dynamic Modulus and Fatigue in Asphalt Mixtures with Blast Oxygen Furnace Slag and Blast Furnace Dust

Abstract: Slag from a Blast Oxygen Furnace (BOF) is produced during the transformation of cast iron, coming from the blast furnace, into steel during the integrated steelmaking process, just as blast furnace dust (BFD) is produced during the transformation of the iron mineral into cast iron. These residues have generated environmental problems due to the accumulation and inadequate disposal thereof. Consequently, this study aims to analyze the use and behavior of the dynamic modulus and the fatigue in asphalt mixtures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Several studies have directed their focus toward repurposing BFDW for some viable applications, e.g., civil construction [28,29], adsorption processes [3,30], briquette production [7,31], and wastewater treatment [5,32]. Recently, Guo et al [33] employed BFDW in producing Fe-C composite electrodes and demonstrated an impressive 95.8% indigo dye removal.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have directed their focus toward repurposing BFDW for some viable applications, e.g., civil construction [28,29], adsorption processes [3,30], briquette production [7,31], and wastewater treatment [5,32]. Recently, Guo et al [33] employed BFDW in producing Fe-C composite electrodes and demonstrated an impressive 95.8% indigo dye removal.…”
Section: Introductionmentioning
confidence: 99%